2017
DOI: 10.1021/acsami.7b01408
|View full text |Cite|
|
Sign up to set email alerts
|

Tunable Nitric Oxide Release from S-Nitroso-N-acetylpenicillamine via Catalytic Copper Nanoparticles for Biomedical Applications

Abstract: The quest for novel therapies to prevent bacterial infections and blood clots (thrombosis) is of utmost importance in biomedical research due to the exponential growth in the cases of thrombosis and blood infections and the emergence of multi-drug-resistant strains of bacteria. Endogenous nitric oxide (NO) is a cellular signaling molecule that plays a pivotal role in host immunity against pathogens, prevention of clotting, and regulation of systemic blood pressure, among several other biological functions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
168
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(177 citation statements)
references
References 69 publications
9
168
0
Order By: Relevance
“…This problem can be addressed by the application of NO. The small molecular size of NO allows it to diffuse through the bacterial biofilm and kill the bacterial cells which are otherwise resistant to bactericidal agents [53, 54]. In other words, the gradually released NO extended the life of BPAM by lowering the concentration of surrounding bacteria near the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem can be addressed by the application of NO. The small molecular size of NO allows it to diffuse through the bacterial biofilm and kill the bacterial cells which are otherwise resistant to bactericidal agents [53, 54]. In other words, the gradually released NO extended the life of BPAM by lowering the concentration of surrounding bacteria near the surface.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, we have shown that SNAP based NO releasing polymers have many desirable properties from a translational perspective such as the long-term storage stability (6 months), ease of sterilization, and extended NO release (> 2 weeks) without negatively affecting the physical characteristics, bacterial inhibition, biocompatibility, and hemocompatibility of the polymer [43, 53, 62, 63]. Similarly, the surface grafted BPAM has been reported to exhibit excellent antimicrobial activity against Gram-positive and Gram-negative bacteria on instant contact due to high surface charge density of the deposited BPAM thin film [20].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of a NO releasing donor molecule such as SNAP in a hydrophobic polymer such as E2As can significantly inhibit the attached viable bacteria on the polymer surface . NO has inherent antithrombotic and antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…NO has inherent antithrombotic and antibacterial properties. It is a cellular signaling molecule which is released at a flux of 0.5–4.0 × 10 −10 mol/mincm 2 in the human body by endothelial cells lining the blood vessels in addition to macrophages and sinus cavities . The unpaired NO electron is extremely reactive and has a very short half‐life of <5 s, allowing it to only have a localized and immediate impact .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation